AN IMPROVEMENT OF CREATIVE PROBLEM SOLVING LEARNING MODEL IN IMPROVING LEARNING ACHIEVEMENT IN AQIDAH SUBJECT - Rahmayani Siregar; Syarifah; Suito (Jurnal Scientia, 2023)
In this study aims to find out how teachers apply the Creative Problem Solving Learning model to improve learning achievement in several subjects in knowing what factors are the obstacles of teachers in using the Creative Problem Solving Learning model, and knowing how the results of the Creative Problem Solving Learning Model in Improving Learning Achievement in Aqidah Ahklak Subjects. The method used in this research is qualitative descriptive analysis method, which is a method to describe the data that has been collected clearly and in detail as it is. While data collection techniques using observation, interviews and documentation. As well as the data sources of this research are students, Aqidah Akhlak teachers, 9th grade guardians, and school principals. The Creative Problem Solving model is a learning model that focuses on learning and problem solving skills, followed by strengthening skills